Akibat Hukum Protokol Notaris Yang Telah Meninggal Dunia Yang Belum Diserahkan Oleh Ahli Waris - Wahyu Sudhyatmika, Ida Bagus Kade; Made, Swardhana Gde (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
The purpose of this study was to find out and analyze the procedure for submitting the protocol of a notary who had died and the efforts of the regional supervisory board if the protocol of a notary who had died was not submitted by the heir. The writing of this journal uses a normative type of research where an assessment of applicable laws and regulations is carried out and uses secondary data as the main data. Based on the results of the study, the following conclusions can be formulated: (1) Article 63 UUJN submission of the protocol of a notary who has died to another notary who receives the protocol is carried out no later than 30 (thirty) days by making a report on the submission of the Notary Protocol signed by the submitter, namely heirs of a notary who has died; and (2) The submission of the protocol of a notary who has died to a notary who receives the protocol is also the authority of the Regional Supervisory Council based on Article 63 of the UUJN which states that if the notary protocol is not submitted within 30 (thirty) days, the Regional Supervisory Council is authorized to take the protocol.